1982
DOI: 10.1113/jphysiol.1982.sp014333
|View full text |Cite
|
Sign up to set email alerts
|

X and Y cells in the lateral geniculate nucleus of macaque monkeys.

Abstract: SUMMARY1. Cells of the lateral geniculate nucleus (l.g.n.) in macaque monkeys were sorted into two functional groups on the basis of spatial summation of visually evoked neural signals.2. Cells were called X cells if their responses to contrast reversal of fine sine gratings were at the f-ndamental temporal modulation frequency with null positons one quarter of a cycle away from positions for peak response. Cells were called Y cells if their responses to such stimuli were at twice the modulation frequency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
347
5
9

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(402 citation statements)
references
References 26 publications
40
347
5
9
Order By: Relevance
“…The cells that present a nonlinear response to contrast and are therefore responsible for this illusion are a subgroup of M cells, called My cells, that overall represent just 3% of all the retinal ganglion cells. 41 FDT showed high sensitivity and specificity in detecting functional impairment of a highly selective and limited cell population, thus demonstrating that it is extremely sensitive for the detection of early alterations in ganglion cells. However, the most intriguing question is, why is a thinning in the RNFL and an increase in the PSD index found with FDT in OH?…”
Section: Discussionmentioning
confidence: 96%
“…The cells that present a nonlinear response to contrast and are therefore responsible for this illusion are a subgroup of M cells, called My cells, that overall represent just 3% of all the retinal ganglion cells. 41 FDT showed high sensitivity and specificity in detecting functional impairment of a highly selective and limited cell population, thus demonstrating that it is extremely sensitive for the detection of early alterations in ganglion cells. However, the most intriguing question is, why is a thinning in the RNFL and an increase in the PSD index found with FDT in OH?…”
Section: Discussionmentioning
confidence: 96%
“…The remaining neurons are those located in the magnocellular layers of the LGN. These receive a broad band chromatic input without color opponency and have a high contrast sensitivity (Kaplan and Shapley, 1982).…”
Section: Nonmorement Pre -Moremmt and Mo~'tvt~nt Unitsmentioning
confidence: 99%
“…It is recognized that the opponent ceils in the parvocellular layers do have some achromatic contrast sensitivity, but their contrast thresholds are very high (Kaplan and Shapley, 1982: Hicks rt ai.. 1983: Lennie rt trl.. 1984) about an order of magnitude higher than cells in the magnocellular layers. at least for medium and low spatial frequencies.…”
Section: Nonmorement Pre -Moremmt and Mo~'tvt~nt Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study based on the model [42] reported that well-defi ned LGN spike trains reduce the noise and elevate the response to the preferred stimulus. It is known that the relay cells are distributed nonrandomly in the LGN of cats and monkeys [43][44][45][46][47] . So the alignment of the receptive fields of relay cells in the LGN [1,5,7,8] could also …”
Section: Mr and Orientation Selectivitymentioning
confidence: 99%